Gender Participation on Rice Post-harvest Activities in Bangladesh (Journal of Environmental Science and Natural Resources, 2015)
The study was undertaken to examine the extent of women along with men participated in post-harvest activities; to identify the problems and constraints faced by them and find suitable solution from their perception. The post-harvest activities were estimated at farm level in Aman rice at Rangpur, Nilphamari, Khulna, Satkhira and Jessore district of Bangladesh by using survey data collected randomly from 270 rice growing households for the year 2012-13. It employed participatory approaches to investigate farmers perceptions on post-harvest management. The analyses shows women spends more time (591 hours ha-1) on PH activities than men (581 hours ha-1) but the ultimate decision maker of those activities are male indicating that women are very seldom given the opportunities to implement their ideas for execution although they are now gaining the right to give their opinion because of social awareness.J. Environ. Sci. & Natural Resources, 8(1): 45-50 2015